Economic valuation of forest resources: current status and the way forward - Abdul Ghani, Awang Noor (Jabatan Perhutanan Semenanjung Malaysia, 2010)
Forests resources contribute significantly to the socio-economic development of the country in the last few decades in terms of ecology, environment, social and economic functions. The majority of forest resources, especially its ecological and environmental functions have no market price and they have been largely ignored in the decision making process or given low priority when the forest land is to be converted to other uses. As such, the policy makers tend to put high priority for other land use options compared to that of forest conservation or protection. Economic valuation.of forest resources have been undertaken by many researchers ranging from simple to complex methodological approach. The studies also cover wide range of goods and services under different forest ecosystems. The results of previous studies are very useful in formulating the policy and legal framework towards developing a comprehensive forest resource accounting in Malaysia. This paper attempts to provide a comprehensive overview of previous studies on economic valuation of forest goods and services in Malaysia and identify gaps that could be used as a framework in formulating strategic direction for future studies. Future research direction is important in providing inputs in managing forest areas for long term social benefits.